Emotional Pathways to Engagement: Predicting Academic Engagement through Academic Emotions among High School Girls - Sajadifar , Saham; Namazi, Seyedeh Afsaneh (KMAN Counseling & Psychology Nexus, 2023)
Objective: This study aims to explore the predictive relationship between academic emotions and academic engagement among female high school students. Methods and Materials: Utilizing a quantitative research design, this study surveyed 240 female high school students in Estahban city, employing the Achievement Emotions Questionnaire (AEQ) to measure academic emotions and the Academic Engagement Scale (AES) for academic engagement. The sample was selected through stratified random sampling, and data were analyzed using multiple linear regression analysis in SPSS version 27 to assess the predictive power of academic emotions on engagement. Findings: The results indicate that academic emotions significantly predict academic engagement, accounting for 40% of the variance in engagement levels. Specifically, class-related emotions (B = 2.33, p < .05), learning-related emotions (B = 2.02, p < .05), and test-related emotions (B = 2.20, p < .05) were found to have a positive and significant impact on academic engagement. These findings highlight the nuanced role that different academic emotions play in shaping students’ engagement with their studies. Conclusion: The study underscores the importance of academic emotions as key determinants of academic engagement among high school students. It suggests that positive academic emotions can enhance engagement, while negative emotions may serve as barriers. The findings advocate for the incorporation of emotional support and management strategies within educational practices to foster an environment conducive to student engagement.